On dynamic crushing behavior of honeycomb-like hierarchical structures with perforated walls: Experimental and numerical investigations. (November 2020) - Qin, Qinghua; Xia, Yuanming; Li, Jianfeng; Chen, Shangjun; Zhang, Wei; Li, Kaikai; Zhang, Jianxun
Highlights: Experiments on the dynamic crushing of metal honeycomb-like hierarchical structures with perforated walls are carried out. New failure modes of dynamic crushing of metal honeycomb-like hierarchical structures with perforated walls are obtained. Specific energy absorption of structures of perforations on double walls are larger than those on single walls. Compared with the uniform perforation design, the perforation gradient designs increase the mean crushing stress. Abstract: Hierarchical structures have the potential advantage of enhancing their energy absorption capabilities. Honeycomb-like hierarchical structures are developed and manufactured by perforating on the cell walls consisting of single thickness inclined walls and double thickness vertical walls. The out-of-plane dynamic crushing experiments on metal honeycomb-like hierarchical structures with perforated walls are carried out to explore the failure modes and energy absorption mechanism. The impact failure modes of honeycomb-like hierarchical structures under different impact velocities are obtained. The corresponding numerical simulations are also performed. It is shown that the numerical results are in good agreement with experimental data. The dynamic mean crushing stress of the honeycomb-like hierarchical structures is larger than the quasi-static mean crushing stress. The mean crushing stress, total energy absorption, specific energy absorption of honeycomb-like hierarchical structures of perforations on double walls are larger than those of perforations on single walls with the same mass. Results from parametric study of factors that influence the dynamic crushing response of honeycomb-like hierarchical structures are presented. Compared with the uniform perforation design, the perforation gradient designs increase the mean crushing stress.